An experimental study on the effect of the swimbladder on hearing sensitivity in Ameiurus nebulosus nebulosus (Le Sueur). - Roggenkamp, Petronella Anna (My University, 1956)
This thesis is concerned with the study on the effect of the swimbladder on hearing sensitivity in Ameiurus nebulosus. The investigation has been performed by means of auditory threshold curves in normal catfish and in catfish in which the resonance of the swimbladder was eliminated. The results were compared. The thesis consists of an introduction to the investigation, followed by a review of the literature in relation to the problem, a description of the material and technique and of the experimental work, the results obtained with a discussion and a summary.
Keywords: swimbladder; Ameiurus nebulosus; catfish; animal hearing